Estimating Cost Efficiency of the Banking Sector in China with Stochastic Frontier Analysis - Yang, Shangyuan (2019)
Using the stochastic frontier analysis, our paper investigates the cost efficiency of the Chinese banking industry from 2011 to 2017. Specifically, BC95 model is used and macroeconomic variables are introduced as exogenous variables for analysis. In general, the mean cost efficiency of Chinese banking industry is relatively high. Our results indicate that the macroeconomic factors may have little impact on China’s cost efficiency. Meanwhile, the cost efficiency between several types of Chinese commercial banks is slightly different. Among them, joint-stock banks have the highest cost efficiency score while state-owned banks are in the lowest cost efficiency level. Moreover, banks are found to be more cost-effective in more economically developed regions. These results of this paper reveal the fact that Chinese banking industry still needs further reform and can provide suggestions for the government or regulators to formulate relevant policies.